REPORTS: THE MCGILL CENTRE FOR LEARNING AND DEVELOPMENT - Anderson, Gary J. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1969)
With the estoblishment of a Centre for Learning and Development, McGill recently launched a major drive to encourage reform and innovotion in learning and teaching methods at the university level. The Centre is directed by Marcel Goldschmid of the Department of Psychology, and has a permanent staff of three other professors as well as three research assistants. An advisory board, made up of well-known scholars from Canada and the United States, will oversee its work.